Correlation of methane production with physiological traits in Trichodesmium IMS 101 grown with methylphosphonate at different temperatures - Zou, Chuze; Yi, Xiangqi; Li, He; Bizic, Mina; Berman-Frank, Ilana; Gao, Kunshan (Frontiers in Microbiology, 2024)
The diazotrophic cyanobacterium Trichodesmium has been recognized as a potentially significant contributor to aerobic methane generation via several mechanisms including the utilization of methylphophonate (MPn) as a source of phosphorus. Currently, there is no information about how environmental factors regulate methane production by Trichodesmium. Here, we grew Trichodesmium IMS101 at five temperatures ranging from 16 to 31 °C, and found that its methane production rates increased with increased temperature to peak (1.028±0.040 nmol CH4 μmol POC -1 day -1 ) at 27 °C, and then declined, along with its specific growth rate ranged from 0.03±0.01 d -1 to 0.34±0.02 d -1 , with the optimal growth temperature identified between 27 and 31°C. Within the tested temperature range the Q10 for the methane production rate was 4.6±0.7, indicating a high sensitivity to thermal changes.. In parallel, the methane production rates showed robust positive correlations with the assimilation rates of carbon, nitrogen, and phosphorus, resulting in the methane production quotients (molar ratio of carbon, nitrogen, or phosphorus assimilated to methane produced) yielding 227-494 for carbon, 40-128 for nitrogen, and 1.8-3.4 for phosphorus within the tested temperature range. Based on the experimental data, we estimated that the methane released from Trichodesmium can offset about 1% of its CO2 mitigation effects.